The Cambridge handbook of intelligence - Sternberg, Robert J. (Robert Jeffrey), 1949- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
Written by the foremost experts in human intelligence. It not only includes traditional topics, such as the nature, measurement, and development of intelligence, but also contemporary research into intelligence and video games, collective intelligence, emotional intelligence, and leadership intelligence. In an area of study that has been fraught with ideological differences, this Handbook provides scientifically balanced and objective chapters covering a wide range of topics. It does not shy away from material that historically has been emotionally charged and sometimes covered in biased ways, such as intellectual disability, race and intelligence, culture and intelligence, and intelligence testing. The overview provided by this two-volume set leaves virtually no area of intelligence research uncovered, making it an ideal resource for undergraduates, graduate students, and professionals looking for a refresher or a summary of the new developments.
Title from publisher's bibliographic system (viewed on 18 Dec 2019).
Keywords: elektronické knihy; electronic books; Intellect; Human information processing